2020
DOI: 10.1002/srin.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Casting Secondary Cooling: Laboratory Heat Transfer Measurements and Accuracy Considerations by Comparison with the Real Situation

Abstract: In secondary cooling of continuous casting, it is very important to know the cooling heat flux for the actual spray cooling situation with respect to various parameters like the local position, the nozzle types, distances, and the water and air flow rates, to be able to control the cooling conditions precisely. As heat flux measurements on a casting machine are too challenging, experimental laboratory test rigs are designed and used for measurements by different research groups. Therefore, metal probes of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Detailed study of what can make differences in the published data can be found in the study by Javurek and Mittermair. [ 22 ] It will be further discussed how the parameters are defined in this study and how the results should be used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed study of what can make differences in the published data can be found in the study by Javurek and Mittermair. [ 22 ] It will be further discussed how the parameters are defined in this study and how the results should be used.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, the faster the relative movement is, the greater asymmetry and the lower the maximal HTC value is observed. [ 22 ] The HTC results based on a stationary experiment should be used in applications with caution where relative motion occurs. Experimental data published in this article were obtained for velocity of 1 m min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Xia and Schiefermüller pointed out that the contact length between the slab and roll has an important influence on the distribution of temperature and stress–strain of the roll in the secondary cooling zone and found that the maximum stress on the support roll under this experimental condition was less than 70 Mpa. Javurek et al compared heat transfer models of rolls with different dimensions and proposed mathematical models with different complexities to calculate the temperature of the slab and roll. Zhu, Pujilaksono, and Bruckel et al studied the oxidation behavior of roll steel under dry and humid conditions, results indicated that the water vapor in the oxidation atmosphere can accelerate the oxidation of the roll.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [6] developed a model for accurately predicting spray formation from flat-fan atomizers and the heat transfer between impinging droplets and a moving hot steel slab. Javurek et al [7] analyzed the variation of heat flux data under different nozzle spray cooling conditions and applied it to the actual secondary cooling process control of continuous casting. Kotrbacek et al [8] analyzed the influence of impact density and impact pressure of spray water on the heat transfer efficiency of continuous casting slab and created the relevant quantitative function of heat transfer coefficient.Secondary cooling control is an important content in the continuous steel casting process.…”
mentioning
confidence: 99%